Contemporary western ethnography and the definition of religion - Stringer, Martin D. (Continuum advances in religious studies, 2008)
On defining religion -- On ethnography -- Of requiems and reincarnation -- Of graveyards and kitchens -- Of starsigns and soap operas -- On gender -- On the elementary form of religious life